2015
DOI: 10.1073/pnas.1413835112
|View full text |Cite
|
Sign up to set email alerts
|

Transmission potential of Rickettsia felis infection by Anopheles gambiae mosquitoes

Abstract: A growing number of recent reports have implicated Rickettsia felis as a human pathogen, paralleling the increasing detection of R. felis in arthropod hosts across the globe, primarily in fleas. Here Anopheles gambiae mosquitoes, the primary malarial vectors in subSaharan Africa, were fed with either blood meal infected with R. felis or infected cellular media administered in membrane feeding systems. In addition, a group of mosquitoes was fed on R. felisinfected BALB/c mice. The acquisition and persistence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
101
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 138 publications
(107 citation statements)
references
References 42 publications
4
101
0
2
Order By: Relevance
“…(1) on our work (2), and agree that the number of animals, including leeches and arthropods, playing a role in the transmission of Rickettsia felis might be greater than previously suspected. In the Slesak et al…”
supporting
confidence: 79%
“…(1) on our work (2), and agree that the number of animals, including leeches and arthropods, playing a role in the transmission of Rickettsia felis might be greater than previously suspected. In the Slesak et al…”
supporting
confidence: 79%
“…Moreover, R. felis has been identified by molecular detection from the blood, skin, and internal organs of suspected reservoir hosts (Abramowicz et al 2011; Kuo et al 2015; Panti-May et al 2014; Schriefer et al 1994b; Tay et al 2015; Tay et al 2014), but viable bacteria have never been isolated from these tissues. A recent study generated R. felis -infected mice (inbred mouse strain BALB/c) via an artificial inoculation route, and subsequently produced infectious Anopheles gambiae mosquitoes that caused transient rickettsemia in naïve mice (Dieme et al 2015); however, naturally infected mammalian blood or tissues have never been shown to be a source of R. felis infection from vertebrate to arthropod host (Weinert et al 2009). Additionally, much debate surrounds the likelihood of freely circulating rickettsiae in the blood of vertebrates from non-fatal cases (Labruna & Walker 2014).…”
Section: Introductionmentioning
confidence: 99%
“…4 Similar age and seasonality patterns of infection, along with the recently reported potential of Anopheles gambiae mosquitoes to transmit R. felis, have given rise to a new hypothesis on possible common transmission routes of R. felis and malaria. 4,5,13 The clinical significance of R. felis infection and malaria-R. felis coinfection has been controversially discussed. In our study, all patients were febrile, but additional symptoms were nonspecific.…”
mentioning
confidence: 99%